FORMATION OF THE LATE PALEOZOIC STRUCTURE OF THE TELETSK REGION: KINEMATICS AND DYNAMICS (GORNY ALTAI-WEST SAYAN JUNCTION) - Smirnova L.V.; Theunissen K.; Buslov M.M. (My University, 2002)
The Late Paleozoic structure and evolution of the Gorny Altai-West Sayan junction is considered on the basis of geochronology and structural data obtained by morphological, stereometric, and microstructural methods. The distinguished evolution stages of the region (Early-Middle Devonian, Late Devonian-Early Carboniferous, and Permian) fit the general geodynamic setting of the Altai-Sayan folded area. The Early-Middle Devonian stage was marked by intrusion of the Altyntauss granitoids into greenschist rocks. During the Late Devonian-Early Carboniferous stage, the Teletsk shear zone initiated along the eastern margin of the Altyntauss pluton. The formation of the shear zone was accompanied by strike-slip and thrust faulting under NW-SE compression and corresponds to the stage of collision between Siberia and the Altai-Mongolia terrane. According to new data, the northern part of the shear zone may have been produced by thrusting that acted simultaneously with left-lateral strike-slip motions on the master fault (about 80 km of horizontal displacement). The Permian stage corresponds to the Kazakhstan-Siberia collision and was associated with the formation of the North Sayan strike-slip fault under WE compression, with a right-lateral slip of about 30 km. The North Sayan fault truncates and deforms the Late Devonian-Early Carboniferous structural framework.
Keywords: Paleozoic; Paleozoic; Палеозой